PENGOLAHAN DAUN KELOR UNTUK MENAMBAH VARIASI BOLU PANDAN DI éL ROYALE HOTEL BANDUNG - Binur Pretty Napitupulu; Firda Natasya Sinambela (Akademi Pariwisata Darma Agung, 2021)
The Pastry section is under the auspices of the food and beverage product department, which is tasked with processing cakes and breads in the hotel. The pastry section must be able to prepare and produce cakes that are really high quality, healthy and attractive for consumption. There are many variations of cakes at El Royale Hotel Bandung, good and interesting, but the author wants to process the cake recipe from the existing pandan sponge recipe and than vary it by adding Moringa leaves. The author hopes that moringa leaves will not only add variety, but also fulfill the nutrion of consumers. There fore, so that cakes consumed have high nutritional value, the authors want to modify the cake by fortification (adding) the ingredients to the cake by adding Moringa leaves to the pandan sponge processing at El Royale Hotel bandung. The author conducts direct research through interviews and observations during the production process of pandan sponge cake, the author also looks for theories about moringa leaves and pandanus cake and trials (testfood) in the laboratory of the Darma Agung Medan tourism and hospitality Academy. Trials (experiments) were Carried out for 2 (two) months. The process of processing Moringa leaves are added to add nutrion. The results of making moringa leaf pandanus sponge are very good and interesting as evidenced by the results of trials that have been assessed. Well by the campus community who have given positive comments and like moringa leaf pandanus sponge. The author hopes that this moringa pandan sponge , recipe can be recommended to be processed in the kitchen of El Royale hotel Bandung as a healthy snack.